The Ford Resource And Engagement Centre (FREC) Programme’s contribution to mitigate poverty : perspectives from participants - Chiwara, Peggie (University of Pretoria, 2024)
Mini Dissertation (MSW (Social Development and Policy)--University of Pretoria, 2024.